2017
DOI: 10.1111/apa.13679
|View full text |Cite
|
Sign up to set email alerts
|

Active commuting to school was inversely associated with academic achievement in primary but not secondary school students

Abstract: Active commuting to school was inversely associated with academic achievement in primary school students but not those at secondary school. Longitudinal and intervention studies are needed to further understand our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 32 publications
0
29
0
5
Order By: Relevance
“…All of the studies had approximately 50.00% girls as a part of their sample, with the lowest and the highest percentage being 42.47% [44] and 53.26% [42], respectively. Most of the studies (n = 10) were cross-sectional studies [42,[45][46][47][48][49][50][51][52][53], and two were prospective studies [43,44]. Eight studies accounted for socioeconomic status either by asking their socioeconomic status or by using parental education as a proxy for it.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies had approximately 50.00% girls as a part of their sample, with the lowest and the highest percentage being 42.47% [44] and 53.26% [42], respectively. Most of the studies (n = 10) were cross-sectional studies [42,[45][46][47][48][49][50][51][52][53], and two were prospective studies [43,44]. Eight studies accounted for socioeconomic status either by asking their socioeconomic status or by using parental education as a proxy for it.…”
Section: Study Selectionmentioning
confidence: 99%
“…All studies measured active commuting in the context of commuting to school; either to, from or both. Seven studies [43,45,[48][49][50][51][52] reported the percentage of their sample that engaged in active commuting, and it ranged from 12.00% to 70.41%.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations